Shape Preserving Piecewise KNR Fractional Order Biquadratic C2 Spline - Syed Khawar Nadeem Kirmani; Muhammad Bilal Riaz; Fahd Jarad; Hayder Natiq Jasim; Aytekin Enver (Journal of Mathematics)
In a recent article, a piecewise cubic fractional spline function is developed which produces C1 continuity to given data points. In the present paper, an interpolant continuity class C2 is preserved which gives visually pleasing piecewise curves. The behavior of the resulting representations is analyzed intrinsically with respect to variation of the shape control parameters t and s. The data points are restricted to be strictly monotonic along real line.